OPTIMIZATION OF BIOETHANOL PRODUCTION FROM GAMBA GRASS (Andropogon gayanus) AND LOVE GRASS (Eragrostis tremula) USING ACID HYDROLYSIS - Muhammad, S. I.; Muhammad, C.; Birnin-Yauri, U. A.; Baki, A. S.; Mohammed, M. L.; Ahmad, B. R. (FUDMA JOURNAL OF SCIENCES, 2023)
Bioethanol is a widely utilized liquid biofuel and demand for it has been increasing, there is a need to enhance production of it from more affordable and environmentally friendly raw materials. In this study Gamba grass and Love grass both were used as resources for the production of bioethanol using dilute acid hydrolysis. Reducing sugar was determined after hydrolysis with UV spectrophotometer at 540 nm with pH values of 4.0, 4.5, and 5.0 of samples and the results were compared. Optimization of process parameters for comparative production of bioethanol from Gamba grass and Love grass using Saccharomyces cerevisiae were carried out using Response surface based on Box-Beinkhen design. The optimum yield of bioethanol from sample A was 69.0% and sample B was 67.0% at the temperature, pH and reaction time of 32.5°C, 5.0, 120 hours respectively. This research shows that Gamba grass has the highest yield of bioethanol when compared with Love grass. The studies revealed suitability of both Gamba and Love grass as potential sources of good quality bioethanol.
Keywords: Bioethanol; Gamba grass; Love grass; Saccharomyces cerevisiae; Acid hydrolysis